Boglár, Lelle vagy Boglárlelle: : a közös időszak gazdasági változásai - Wilhelm, Réka (Közép-Európai Közlemények, 2024)
The aim of this study is to provide a comprehensive overview of the developments in Boglárlelle from 1978 to 1991, contextualised within the economic development of present-day Balatonboglár and Balatonlelle. It describes the economic changes of the towns over the centuries, the circumstances and the process of their union and separation. Last but not least, it briefly explores the developments that followed their independence in 1991, in an attempt to create a tourist industry that was adapted to the conditions of a modern market economy. In my research, I used literature, contemporary press materials, archival and museum sources, and statistics to learn about the major developments and economic changes of the period of nearly 13 years of Boglárlelle. As a result of the research, I put into context the 13-year common period of Balatonlelle and Balatonboglár and the developments of this period. I found that in 1978, the year of their union, Balatonboglár and Balatonlelle had different economic roles in the region apart from tourism, so the idea of their symbiotic development was well founded. However, while the aggregate figures for the common period (population growth, significant public utility development, etc.) showed progress, the figures for the individual areas of Lelle and Boglár show significant inequalities. The study has demonstrated the relevance of the concept of forced marriage as a characteristic of Boglárlelle, which is also confirmed by the new developments in the independent towns after the separation in 1991.